Digital Tales Media to Improve Reading Literacy for II Grade Elementary School Students - Musyaffa, A A; Asiah, Siti; Rapiko; Fadhil, Muhammad; Ubaidah, Siti (LPPM Undiksha, 2023)
The problem occurs in the learning process, where elementary school students are less motivated to understand material in the form of stories without pictures. Therefore, the researcher conducts this study to develop digital fairy tale media that is applied to second grade of elementary school students. This research is a type of research and development (R&D) or research and development according to Bord and Gall. The steps taken in this research and development, namely: research and data collection, planning, initial product development, initial field trials, revision of trial results, field trials, product enhancements that have been refined, field implementation trials, product improvement final, cementation and implementation. The research subjects were elementary school students. The product produced in this research is digital fairy tale learning media which was developed to add a variety of media. The results of the study show that the digital fairy tale learning media developed using the Bord and Gall model has been declared valid. Based on the material assessment it obtained a percentage of 75% with valid criteria, language assessment obtained a percentage of 95.45% with very valid criteria, and the media assessment obtained a percentage of 86.45% with very valid criteria. From students obtained through product trials in small groups, namely obtaining a score percentage of 90.52% with very valid criteria, and large group field trials obtaining a score percentage of 95.40% with very valid assessment criteria, and has a level of effectiveness of 93.63%.